Role of drug information center in detecting medication errors in a tertiary care hospital, central region, Saudi Arabia - Omar Yahya Ahmed Alshargi; Nader Ayedh Albalagi; Admin (Journal of the Pakistan Medical Association, 2023)
Objective: To identify the incidence of medication error in a tertiary care hospital and to document the role of drug information centre to prevent such errors. Methods: The retrospective cross-sectional study was conducted at the Security Forces Hospital, Riyadh, Saudi Arabia, and comprised review of secondary data collected from the Drug Information Centre from March 2013 to February 2016. The errors were categorised as under-prescribing, dispensing, administrating and transcription, while the received inquiries were classified according to the inquirer; physicians, pharmacists and nurses. The score was given according to the Grade of Severity scale. Data was analysed using IBM SPSS Statistics for Windows, version 20. Armonk, NY: IBM Corp. Categorical variables were presented as frequency and percentage. Results: Among the 2800 drug-related inquiries received, 238(8.5%) medication errors were detected. The inquirers of these queries included 108(45.4%) nurses. Administration errors were the highest 113(47.5%), while the least were transcription errors 31(13%). Majority of errors were committed by nurses 113(47.5%). Grade 2 errors were the most common 86(36.10%), while grade 4 life-threatening errors were minimal 2(0.8%). There were significant differences in the number of received questions based on the specialty (p 0.05), staff having committed the error (p 0.01) and the type of errors detected (p 0.01). Conclusion: The prevalence of medication errors committed by healthcare providers was high. Key Words: Medication error, Drug information centre, Administration, Physician, Pharmacist.